2018
DOI: 10.1021/acs.jpcc.8b06644
|View full text |Cite
|
Sign up to set email alerts
|

SEIRAS Study of Chloride-Mediated Polyether Adsorption on Cu

Abstract: Surface-enhanced infrared absorption spectroscopy is used to examine the co-adsorption of a selection of polyethers with Cl– under conditions relevant to superconformal Cu electrodeposition in CuSO4–H2SO4 electrolytes. In 0.1 mol/L H2SO4, a potential-dependent mixed SO4 2––H3O+/H2O layer forms on weakly textured (111) Cu thin-film surfaces. With the addition of 1 mmol/L NaCl, the SO4 2––H3O+/H2O adlayer is displaced and rapidly replaced by an ordered halide layer that disrupts the adjacent solvent network, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 113 publications
(457 reference statements)
6
77
1
Order By: Relevance
“…1 – 8 Halide adsorption by itself leads to acceleration of the copper deposition rate while polyether co-adsorption on the halide adlayer gives rise to significant inhibition of copper deposition by limiting access of Cu 2+ aq to the metal surface. 1 – 26 Electroanalytical, 1 – 26 gravimetric microbalance, 14 , 15 ellipsometry 18 and vibrational spectroscopy 27 , 28 studies unambiguously demonstrate that halide adsorption is required for co-adsorption of an effective polyether suppressor layer. Co-adsorption involves factors from the multiplicity of halide-polyether binding sites, 24 to halide perturbation of interface water structure that makes it more hydrophobic favoring polyether adsorption, 28 to a possible role of Cu + as an ether-halide binding agent.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…1 – 8 Halide adsorption by itself leads to acceleration of the copper deposition rate while polyether co-adsorption on the halide adlayer gives rise to significant inhibition of copper deposition by limiting access of Cu 2+ aq to the metal surface. 1 – 26 Electroanalytical, 1 – 26 gravimetric microbalance, 14 , 15 ellipsometry 18 and vibrational spectroscopy 27 , 28 studies unambiguously demonstrate that halide adsorption is required for co-adsorption of an effective polyether suppressor layer. Co-adsorption involves factors from the multiplicity of halide-polyether binding sites, 24 to halide perturbation of interface water structure that makes it more hydrophobic favoring polyether adsorption, 28 to a possible role of Cu + as an ether-halide binding agent.…”
mentioning
confidence: 92%
“…1 – 26 Electroanalytical, 1 – 26 gravimetric microbalance, 14 , 15 ellipsometry 18 and vibrational spectroscopy 27 , 28 studies unambiguously demonstrate that halide adsorption is required for co-adsorption of an effective polyether suppressor layer. Co-adsorption involves factors from the multiplicity of halide-polyether binding sites, 24 to halide perturbation of interface water structure that makes it more hydrophobic favoring polyether adsorption, 28 to a possible role of Cu + as an ether-halide binding agent. 9 , 11 , 27 Upon polarization to negative potentials the inhibition breaks down and the electrode bifurcates into active plating versus passive regions that subsequently yields significant voltammetric hysteresis.…”
mentioning
confidence: 92%
“…For low Cl − concentration, suppression breakdown is determined by flux limitation on the Cl − whose co-adsorption is required to form the blocking polyether-Cl − suppressor phase. 13 The transition from passivated surface to active deposition is localized at fixed depth in the TSV that reflects the balance point between the concentration- and transport-dependent rate of halide adsorption onto the surface and the potential-dependent rate of its removal by consumption. 12 This is congruent with previous S-NDR bifurcation models of feature filling that capture discontinuous deposition within features due to gradients in additive and metal ion concentration that translate to potential-dependent depth of suppression breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Among the systems examined are electrolytes containing poloxamine and chloride that co-adsorb to form the suppressor layer that underlies bottom-up Cu filling of 56 μm deep annular TSV. 4 , 13 Feature filling based on this additive system has been explored over a broad range of deposition conditions in electrolytes containing 1 mmol/L Cl − and 20 μmol/L to 80 μmol/L poloxamine 11 (variable polyether and fixed high Cl − ) as well as electrolytes containing 20 μmol/L to 80 μmol/L Cl − and 40 μmol/L poloxamine (fixed polyether and variable low Cl − ). 12 A single additive S-NDR model, based on disruption of the passivating polyether by metal deposition with the kinetic parameters obtained from electroanalytical measurements under well-defined hydrodynamics, captures the experimental TSV filling in the high-Cl − electrolytes for a range of micromolar polyether concentrations.…”
mentioning
confidence: 99%
“…Increasing ratio of gauche conformers upon adsorption was consistent with experimental and theoretical studies of PEG adsorption, which indicated a reorientation from predominantly trans conformations in solution to gauche. [25,28,29] Similar to the previous studies, we used surface-enhanced Raman spectroscopy (SERS) for conformational analysis of PEI on the chloridecovered Cu surface (Figure 6). Peaks a and b are assigned to symmetric and asymmetric CH 2 stretching modes.…”
Section: Structural Analysis On the Surfacementioning
confidence: 99%